War Syndrome and The Labour Market: The Impact of The Development of Post-Traumatic Stress Disorder in Employees and Subsequent Problems in Professional Life on The Example of Victims of The Russian-Ukrainian War - Daniil POLIAKOV; Jacek WINIARSKI (Communications of International Proceedings, 2023)
The agenda of this research is to study the impact of Post-traumatic stress disorder (PTSD) on the professional qualities of employees, the difficulties they began to face after the appearance of the syndrome, as a result - the second one purpose, is development of recommendations directly for such employees, who suffering or highly risking to shuffle on PTSD, which will help to avoid or at least reduce possible negative aspects. The research design involves the use of anonymous questionnaires for the survey. The research is designed in such a way to determine the degree of damage to the respondent and the relationship with emerging difficulties in the professional field (such as the appearance of difficulties in performing creative, communicative, monotonous, or other activities) and in the labour market (for example, finding a new place of work, key motivators for keeping or changing work). The study was developed in the situational context of the Russian-Ukrainian war.
Keywords: Post-traumatic stress disorder (PTSD); War Syndrome; Labour market